Supporting and Contradicting Views of Thoughts on Isrāʾīliyyāt - Irham, Irham; Sitorus, Aulhim; Sahputra, Hery (Lembaga Yasin AlSys, 2025)
This study aims to analyze both supporting and opposing scholarly perspectives on the use of Israiliyyat in Qur'anic interpretation. Utilizing a qualitative library research method, the study explores the historical and textual foundations underlying the inclusion of Israiliyyat narratives. Findings indicate that the use of Israiliyyat in tafsir has historical legitimacy, supported by references such as Surah Yûnus verse 94 and several hadiths that permit the narration of stories from the Children of Israel. However, this permissibility is conditional and must be approached with caution. Scholars categorize Israiliyyat into three types: those that align with Islamic teachings, those that contradict them, and those that are neutral. A critical and discerning approach is essential to maintain the authenticity of interpretation and protect the integrity of Islamic faith. When used responsibly, Israiliyyat can enhance the historical depth of interpretation, as seen in the works of classical mufassirs like Ibn Jarir al-Ṭabarī and Ibn Kathīr. Nevertheless, Israiliyyat should not be considered a source of law or creed but rather as supplementary material offering contextual insight. The study concludes that the appropriate use of Israiliyyat requires a balance between intellectual openness and theological vigilance, enabling a nuanced and faithful understanding of its role in Islamic exegesis.